Konstruksi Portofolio di Bursa Efek Indonesia ( BEI ) Dengan Metode Markowitz: Studi Empiris Kompas 100 Periode Desember 2014-September 2023 - Sumi Lala; Alder Haymans Manurung; Wirawan Widjanarko; Muhammad Asif khan; AWN Fikri (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
Sumi Lala.202010325238. Portofolio Construction On The Indonesia Stock Exchange (BEI) Using The Markowitz method (Empirical Study Of Kompas 100 period December 2014 – September 2023). Investment development is currently very rapid. Ownership of 2 or more items can called a portofolio.Investments will experience increases and decreases in the portofolio. This research aims to understand the level of  return of portofolios formed through Markowitz and also a comparison between portfolios returm with market capitalization and weighting. The shares in the portfolio are shares listed on the Kompas 100 Index. This research uses end of month data for the period December 2014 to September 2023.The results of this research found that 61 shares included in the portolio did not have a negative weight.the next result of this research is that the market rate of return portolio (IHSG) Significantly influences the rate of return of the portfolio that has been formed based on market capitalization significantly 1% Other macro variables US Dollar exchange rate.Interest rates and oil prices do not significantly affect the rate of return portfolios formed based on Market Capitalization.